Studi Literatur: Analisis Review Audit Deteksi Fraud - Indhira Ridho Abdhilla; Siti Lailatus Saidah; Rizky Abdul Karim; Titus Gustiagung Grace Widya Arta; Tri Ratnawati (Universitas Katolik Widya Karya Malang, 2023)
The purpose of this study is to find out the methods used by an auditor to detect fraud effectively and to find out the factors that cause fraud. This research method uses descriptive qualitative methods, using secondary data literature studies, in the form of journals and articles. The data source in this study uses literature from research journals, related papers and articles. Sample selection is done by observing and analyzing various information related to research by collecting some relevant literature, which aims to integrate the findings with the same topic.